Causal analysis of nitrogen oxides emissions process in coal-fired power plant with LiNGAM - Saito, Tatsuki; Fujiwara, Koichi (Frontiers in Analytical Science, 2023)
Coal has been an important energy source worldwide; however, it is the largest source of nitrogen oxide (NOx) emissions because the amount of nitrogen in coal is larger than that of other fossil fuels. Precise control of NOx emissions is required in operations of coal-ﬁred power plants from the viewpoint of air pollution control. Although theoretical analyses of NOx generation from a coal-ﬁred power plant have been conducted, it is difﬁcult to precisely predict NOx generation in an actual plant. NOx generation is affected by various factors, such as furnace design and operating conditions, and there are complicated relationships among them. Thus, it is necessary to identify important operating factors that affect NOx generation in actual coal-ﬁred power plants. A linear non-Gaussian acyclic model (LiNGAM) is an exploratory causal analysis method that identiﬁes a causal ordering of variables and their connection strengths without any prior knowledge of causal relationships among variables. In this study, we analyzed real operation data collected from a coal-ﬁred power plant using LiNGAM to identify factors of NOx generation. The causal relationship between process variables and NOx generation was estimated by means of LiNGAM, and the connectional strengths of the variables on NOx generation were derived. The analysis results agreed with previous reports on NOx generation mechanisms, such as combustion air temperature, steam temperature on a speciﬁc side of the furnace, and air ﬂow rate of forced draft fans. In addition, we found the steam ﬂow rate and the furnace pressure as new candidate factors of NOx generation through causal analysis using LiNGAM, which heretofore has not been suggested. Our analysis result should contribute to reducing NOx emissions from coal-ﬁred power plants in the future.